Muslim Resistance: Review of Health Policies for Pandemic Mitigation - Tri Endah Karya Lestiyani; Yudi Armansyah; Muhammad Fahmi Fajar (Jurnal Ilmu Pemerintahan)
This research examines the resistance of Muslims to the policy of handling the co-19 pandemic implemented by the Jambi city government in limiting and prohibiting congregational prayer activities, wedding celebrations, and Lebaran homecoming. This research collects qualitative data obtained through observation, interviews, and documentation. From the findings, and data analysis, it is known that: First, the resistance carried out by Muslims is due to the communication and socialization carried out by the government in the covid-19 countermeasure policy has not been effective, especially at the beginning of its implementation, both physical distancing, new normal, PSBB, and PPKM policies. However, the resistance that occurs is only among the grassroots - ordinary people. On the other hand, groups of Islamic religious leaders, and leaders of mass organizations mostly accept the policies implemented by the government, until resistance automatically disappears along with the improvement of policies carried out by the government.